2018
DOI: 10.1186/s12951-018-0410-x
|View full text |Cite
|
Sign up to set email alerts
|

Combustion-derived particles inhibit in vitro human lung fibroblast-mediated matrix remodeling

Abstract: BackgroundThe continuously growing human exposure to combustion-derived particles (CDPs) drives in depth investigation of the involved complex toxicological mechanisms of those particles. The current study evaluated the hypothesis that CDPs could affect cell-induced remodeling of the extracellular matrix due to their underlying toxicological mechanisms. The effects of two ultrafine and one fine form of CDPs on human lung fibroblasts (MRC-5 cell line) were investigated, both in 2D cell culture and in 3D collage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…The smaller particles, ultrafine particles (UFPs), have been shown to localize to mitochondria of endothelial cells, where they induce major structural damage (67). Combustion-related particles have also been shown to cause mitochondrial structural damage in lung cells (68,69). Studies on placentas exposed to higher levels of air pollution show placental mitochondrial DNA methylation (70) and decreased placental mitochondrial DNA content (71).…”
Section: Discussionmentioning
confidence: 99%
“…The smaller particles, ultrafine particles (UFPs), have been shown to localize to mitochondria of endothelial cells, where they induce major structural damage (67). Combustion-related particles have also been shown to cause mitochondrial structural damage in lung cells (68,69). Studies on placentas exposed to higher levels of air pollution show placental mitochondrial DNA methylation (70) and decreased placental mitochondrial DNA content (71).…”
Section: Discussionmentioning
confidence: 99%
“…The dual-channel multiphoton microscopy measurements on CDPs and non-CDPs as reference for particulate air-pollutants were performed on NP suspensions in buffered medium and ultrapure water at biologically relevant concentrations of 20 mg ml À1 . 37,38 The light emitted by the particles was detected simultaneously in two separate channels, which are available with most multiphoton microscopes in biomedical research laboratories, as shown in the schematic in Fig. 1a and b.…”
Section: Resultsmentioning
confidence: 99%
“…We have employed 4 different commercially available CDCPs with different sizes, according to their specifications, to test the abilities of the setup for their selective detection and size determination in aqueous suspensions using biologically relevant concentrations (20 µg/mL). 32,33 Before measuring using DCMPFC setup, the non-incandescence related WL emission of the CDCPs suspensions under illumination with a fs-pulsed NIR laser at 780 nm was double-checked (Figure S2). This emission spectrum shows that the unique WL emitted by CDCPs covers the whole visible spectrum, and hence can be detected in the VISC.…”
Section: Dual-channel Detection Of Cdcps Based On Wl Emission and Sca...mentioning
confidence: 99%